Interactive English language learning: DishZle language game / Aiza Johar ... [et al.] - Johar, Aiza; Morni, Affidah; Sahari, Siti Huzaimah; Kamri, Thalany; Awang Shuib, Awang Rozaimie (Universiti Teknologi MARA Cawangan Sarawak, 2018)
English language learning is often perceived as a static mode of classroom learning activities. Hence, interactive teaching materials are necessary for grabbing learners’ attention span and interests, and in enhancing their involvement. DishZle - a 2-in-1 self-designed language game, focuses on vocabulary and sequencing activities. DishZle deals with various local traditional Malaysian dishes. Hence, the game introduces the learners to the special and unique ingredients and the processes involved in preparing the dishes. They can develop their knowledge of local dishes and improve their proficiency in the English language (speaking, vocabulary and linkers). The game is suitable for beginner to intermediate learners of English (as lead-in activity or post activity of a lesson) in which it introduces cultural topics, which are related to local dishes to their students. This study is a preliminary study to identify the participants’ reactions towards DishZle (effectiveness of using this game in learning the vocabulary and sequencing skills), language learning challenges they face during the game and suggestions to improve the game. The method used was a semi-structured interview, involving 17 participants (diploma students). Most participants claimed that both games were interesting, fun, interactive (communicate with team members) and informative (learn new words and steps to prepare local dishes). It is recommended that language games can often be used as part of teaching methods in ESL classroom as they enhance fun learning, communicative competency, teamwork and cooperation as well as develop English language components (vocabulary and sequencing , in the context of this study.)